2016
DOI: 10.1002/jnr.23745
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory effect of norepinephrine on neurons in the inferior vestibular nucleus and the underlying receptor mechanism

Abstract: The central noradrenergic system, originating mainly from the locus coeruleus in the brainstem, plays an important role in many physiological functions, including arousal and attention, learning and memory, anxiety, and nociception. However, little is known about the roles of norepinephrine (NE) in somatic motor control. Therefore, using extracellular recordings on rat brainstem slices and quantitative real-time RT-PCR, we investigate the effect and mechanisms of NE on neuronal activity in the inferior vestibu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In the normal state and in the absence of threat, the tonic LC-NE system sustains vigilance and orienting functions ( David Johnson, 2003 ). At an early, basic level, LC projections to vestibular nuclei mediate vestibulo-ocular and vestibulospinal reflexes for alerting and vigilance ( Balaban, 2002 , 2016 ; Peng et al, 2016 ). The ability of the LC to direct attention to a given cue seems unrelated to valence ( Berridge and Waterhouse, 2003 ): the LC responds to all novel stimuli and mediates general attentional orienting ( Sara and Bouret, 2012 ; Usher et al, 1999 ).…”
Section: Lc Modulation Of Arousal Attention and Memory Formationmentioning
confidence: 99%
“…In the normal state and in the absence of threat, the tonic LC-NE system sustains vigilance and orienting functions ( David Johnson, 2003 ). At an early, basic level, LC projections to vestibular nuclei mediate vestibulo-ocular and vestibulospinal reflexes for alerting and vigilance ( Balaban, 2002 , 2016 ; Peng et al, 2016 ). The ability of the LC to direct attention to a given cue seems unrelated to valence ( Berridge and Waterhouse, 2003 ): the LC responds to all novel stimuli and mediates general attentional orienting ( Sara and Bouret, 2012 ; Usher et al, 1999 ).…”
Section: Lc Modulation Of Arousal Attention and Memory Formationmentioning
confidence: 99%
“…Originating from the locus coeruleus and nucleus subcoeruleus, noradrenergic fibers have been found to terminate in the vestibular nuclei [19]. Additionally, it has been found that norepinephrine can elicit an excitatory response in a concentrationdependent manner on inferior vestibular nucleus neurons [20]. The inferior vestibular nucleus, as the largest nucleus of the vestibular nuclear complex within the brainstem, receives input from the vestibular nerve, carrying information from the saccule and posterior semicircular canal [21].…”
Section: Table 1: Tricyclic Antidepressants and Their Potential Effec...mentioning
confidence: 99%
“…They indicated that NA modifies GABA responses through the activation of likely postsynaptic α 2 - and/or β-adrenoceptors ( Table 1 ). In the inferior vestibular nucleus, NA directly regulates the excitability of neurons by the activation of α 1 -, α 2 - and β 2 -adrenoceptors ( Peng et al, 2016 ). In any case, NA-mediated alteration of neuronal activity in each of these nuclei would have functional significances.…”
Section: Large Glutamatergic Neurons In the Dcnmentioning
confidence: 99%